Recovery of rescuers from a 24-hour shift and its association with physical fitness - Lyytikäinen, Katariina (2013)
The work of rescuers can be physically and psychologically very demanding so it is important for them to have sufficient recovery between work shifts. The purpose of this thesis was to study recovery of rescuers and to see if physical fitness is associated with recovery from work shifts. Heart rate variability (HRV) recordings reflect changes in the autonomic nervous system, and they were used for the analysis of stress and recovery. HRV was recorded for 96 hours, from the beginning of a 24-hour work shift to the beginning of the next shift. Physical fitness assessment included VO2max estimation with a submaximal bicycle ergometer test, and maximal strength testing (isometric bench press and leg dynamometer). Salivary cortisol samples were collected 0, 15, and 30 min after awakening on the three resting days. Some HRV parameters showed enhanced autonomic control after the work shift. Stress percentage decreased from the work day to the 2nd rest day (p<0.05) and relaxation percentage increased after the work shift, but this increase was non-significant. Enhanced autonomic control did not extend to the last resting day in all variables. Square root of the mean squared differences between successive normal-to-normal intervals (RMSSD) and total power decreased with increasing rest. Maximal oxygen uptake (VO2max) was associated with enhanced parasympathetic cardiac control. The effects of lower- and upper-body strength on recovery were less consistent, although increased lower body strength was in many cases associated with enhanced recovery. Cortisol awakening response was attenuated right after the work shift. In conclusion, some parameters reflecting autonomic control were enhanced after work shift and aerobic fitness was associated with increased recovery, but some of the results were inconsistent.